(3TQM QhVI GdJbQjQs - (3CHh GdMSf Ydj Hf CHj eMeO Hf CHj SYO Hf GdMSf GdOjhGfj GdhGSWj, CHh GdMSf GdhGSWj,J (B743 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQafG HJdGhI cJGHg Gdecfhf hLYdfG ef MaGX cdGeg GdeUhf GdPi GeJKd ChGeQg GdYGQahf s
(3BNQgG (B:s
(3Gddge GLYdfG ef eMHjge hGMTQfG ai ReQJge Bejf jG QH GdYGdejf s
(3GdcJGH GdeTQhM(B: (3QhVI GdJbQjQ ai GdNda Hjf GdEQTGO hGdJjSjQs
(3ddeDda CjVGs
(3HgG fXGe GdJYbjHIs
(3Ydi dhMI GdYfhGf Jedc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B157s
Keywords: (3GdbQGAGJ hGdJLhjOs